2011
DOI: 10.14447/jnmes.v14i2.122
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Gas Production by Methane Partial Oxidation on Ni/Fe<sub>3</sub>O<sub>4</sub>-Ce<sub>0.75</sub>Zr<sub>0.25</sub>O<sub>2</sub> Catalysts: Kinetic Study

Abstract: Fe3O4-Ce0.75Zr0.25O2 (FeCZ) is an oxygen carrier material aimed to produce syngas through methane partial oxidation in absence of oxygen gas feed. The objective of the present research is to study the catalytic effect of Ni on FeCZ using an evaluation of the global kinetics (activation energy, reaction rate, order and constant) of its reaction with methane for syngas production. FeCZ and 0.05NiFeCZ (Ni/Fe = 0.05 molar ratio) were synthesized through co-precipitation of their precursor nitrate salts, while 2NiF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hosseini et al [ 15 ] reported the range of activation energies as 60–81 kJ/mol for CeO 2 ‐Fe 2 O 3 oxygen carriers with low or moderate Fe content using a phase boundary‐controlled model. Sosa Vazquez et al [ 16 ] used TGA to investigate the reduction kinetics of three oxygen carriers, namely, Fe 3 O 4 ‐Ce 0.75 Zr 0.25 O 2 (FeCZ), 0.05NiFeCZ (Ni/Fe = 0.05 molar ratio), and 2NiFeCZ. The results indicated that the overall reaction rate of all materials was the first level, and the activation energies of FeCZ, 0.05NiFeCZ, and 2NiFeCZ were 218.4, 165.3, and 118.4 kJ/mol, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Hosseini et al [ 15 ] reported the range of activation energies as 60–81 kJ/mol for CeO 2 ‐Fe 2 O 3 oxygen carriers with low or moderate Fe content using a phase boundary‐controlled model. Sosa Vazquez et al [ 16 ] used TGA to investigate the reduction kinetics of three oxygen carriers, namely, Fe 3 O 4 ‐Ce 0.75 Zr 0.25 O 2 (FeCZ), 0.05NiFeCZ (Ni/Fe = 0.05 molar ratio), and 2NiFeCZ. The results indicated that the overall reaction rate of all materials was the first level, and the activation energies of FeCZ, 0.05NiFeCZ, and 2NiFeCZ were 218.4, 165.3, and 118.4 kJ/mol, respectively.…”
Section: Introductionmentioning
confidence: 99%